Modulation With Metaheuristic Approach for Cascaded-MPUC49 Asymmetrical Inverter With Boosted Output - Kaif Ahmed Lodi (16855518) (2020)
This work introduces a 49-level Asymmetrical Inverter (AMLI) with boosted output based on the cascaded operation of two 7-Level Modified Packed U-Cell inverters (MPUC-7). The converter is capable of operation with a boosted voltage of up to 1.714 times the maximum DC voltage employed. It requires only 12 active switches and 4 voltage sources. With the sources set in the ratio of 14:7:2:1, the 7-level output of the two converters is so utilized that the 7 2 = 49-level output voltage is generated across the load. A detailed explanation of level formation is discussed. This converter is operated using an Artificial Neural Network (ANN) which is trained for the harmonic elimination in the output voltage waveform. For the calculation of optimum angles, a meta-heuristic based Genetic Algorithm (GA) technique is employed. The generation of 49-level output requires 24 transitions in one quarter of a cycle. All these angles are generated for various desired output voltages, and the ANN is trained offline for the same. The converter and its control are simulated in MATLAB/Simulink ® environment, and the results are verified on the experimental setup. The multilevel output thus obtained is nearly sinusoidal and the Total Harmonic Distortion (THD) thus produced is under the specified limit of IEEE. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2020.2995782